Experiments in hydraulic engineering - Singh, Sarbjit (PHI Learning, 2012)
The aim of this book is to enable the students to verify the principles studied in theory by conducting experiments. The book is designed for the undergraduate students of Civil Engineering. This book contains 17 experiments selected from the prescribed syllabi of Hydraulic Engineering and Fluid Mechanics of several universities and institutes. The first part of the book allows the students to review the fundamental theory before stepping into the laboratory environment. The second part provides the step-wise details of each experiment. Appendix A gives various questions based on each experiment to test the student's understanding of the learned material. Appendix B gives data on physical properties of water, air and some commonly used fluids in the laboratory, and also lists the average values of Manning's coefficient to be used in various experiments. The aim of this book is to enable the students to verify the principles studied in theory by conducting experiments.